DEVELOPING A METHOD FOR MEASURING THE QUALITY OF A SAMPLE BASED TRIP LENGTH DISTRIBUTION FOR URBAN TRIP - Suprayitno, Hitapriya; Saraswati, Nina; Fajrinia, Citto Pacama (Rekayasa Teknik Sipil, 2016)
Trip Length Distribution is an important part of Transportation Modelling. This distribution is normally gotten from a sample. Thus, the Quality of the Sample Based Distribution must be able to be measured. This paper present the result of an attempt to develop a method to measure this quality. The research gave the following result. Basic common measure related to the sampling is a maximum acceptable error at a certain minimum confidence level. It has been found that the Quality Measuring Method can not incorporate the error, since it deals with a distribution pattern in which there is no single parameter value and the error probability density function is not yet known. The proposed Sample Quality Measuring Method is by calculating its Confidence Level based on the Goodness of Fit Statistical Inference method, by using a c2 test. The Confidence Level is equal to  P(c2,u);  where  c2 = S (Oi ? Ei)2/ Ei and u = k ? r ? 1. Keywords : transport modelling, trip length distribution, sample, sample quality.